POLITIK HUKUM PERKAWINAN BEDA AGAMA DI INDONESIA (Analisis Mengenai Intervensi Partai Politik terhadap Undang-undang Nomor 1 Tahun 1974 Tentang Perkawinan) - Abdurrahman Hakim (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
This paper aims to analyze the existence of political party intervention in legislative drafting on regulation No 1/1974 about marriage. Political party intervention is actually contrary to responsive legal theory that is applied in the formation of regulations in Indonesia. Political party intervention can change the legal content in the formulation of legislation because there are interests that are subjective. The implication, of course the resulting legal products will not solve problems in society that have been assessed as public issues. If examined from the perspective of public policy, Government intervention is likely to occur at the policy planning stage. This is due to the process, the party as an element of political power views the importance of the values ??of flow in order to be contained in the laws discussed. The result, the regulations that have been passed are far different from the proposed bills. One example is the Marriage regulation. Debate and rejection occur in the discussion of the article 2 (1) UUP 1974. The affiliation of Islamic parties considers marriage to be a matter of worship and religious values. On the other, Nationalist party affiliation refused because it did not reflect reception legal theory.